2012
DOI: 10.4187/respcare.01809
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in COPD Patients, Smokers, and Non-smokers

Abstract: Decreased total antioxidant capacity in plasma of subjects with COPD and smokers suggests an increased oxidative stress in this group. However, no relationship was found between lung function and antioxidant systems status in COPD subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 23 publications
7
56
0
1
Order By: Relevance
“…Our results demonstrated sufficiently Mean difference (COPD group minus control group) is expressed as mean Ϯ SE. SPD ϭ surfactant protein D decreased levels of serum superoxide dismutase 3 in the COPD group compared with the control group and are in agreement with those of Zeng et al, 50 Gavali et al, 51 and Tavilani et al 52 This decreased activity in subjects with COPD probably results from an increase in consumption of antioxidants. 53 We found a superoxide dismutase 3 levels of 244.79 Ϯ 69.12 U/L in the control group (see Table 4), whereas Chakraborty et al 54 reported plasma superoxide dismutase levels of 4.06 Ϯ 0.26 U/mL, KoturStevuljevic et al 55 found plasma superoxide dismutase levels of 153 Ϯ 36 U/L in non-coronary heart disease control subjects, and Comhair et al 56 reported a mean serum superoxide dismutase level of 2.75 U/mL.…”
Section: Discussionsupporting
confidence: 89%
“…Our results demonstrated sufficiently Mean difference (COPD group minus control group) is expressed as mean Ϯ SE. SPD ϭ surfactant protein D decreased levels of serum superoxide dismutase 3 in the COPD group compared with the control group and are in agreement with those of Zeng et al, 50 Gavali et al, 51 and Tavilani et al 52 This decreased activity in subjects with COPD probably results from an increase in consumption of antioxidants. 53 We found a superoxide dismutase 3 levels of 244.79 Ϯ 69.12 U/L in the control group (see Table 4), whereas Chakraborty et al 54 reported plasma superoxide dismutase levels of 4.06 Ϯ 0.26 U/mL, KoturStevuljevic et al 55 found plasma superoxide dismutase levels of 153 Ϯ 36 U/L in non-coronary heart disease control subjects, and Comhair et al 56 reported a mean serum superoxide dismutase level of 2.75 U/mL.…”
Section: Discussionsupporting
confidence: 89%
“…The mRNA expressions of Mn-SOD and Cu Zn-SOD were significantly increased in the lungs of SM-exposed patients [27]. SOD, CAT and GST activities may be increased or decreased in various pulmonary diseases including asthma and COPD [6,11,17,25]. Jafari and Ghanei reported a significant increase in SOD and CAT activities in plasma, erythrocytes, and brochoalveolar lavage fluid (BAL) and GST activity in BAL of patients with SM-induced lung injuries [8].…”
Section: Discussionmentioning
confidence: 99%
“…Volume 11, No 5, September-October2017; http://www.ijt.ir dismutase (SOD), catalase (CAT), glutathione Stransferase (GST) and large amounts of glutathione (GSH) [11]. SM-induced oxidative stress is associated with alteration of antioxidant enzyme activities, depletion of GSH and an increase of membrane lipid peroxidation in tissues, all of which can lead to inflammation and ultimately induction of cell death [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Mak et al (25) showed that erythrocyte catalase activity increased in patients with COPD, which is different from our findings. However, Tavilani et al (26) and some others demonstrated that antioxidant enzyme might be downregulated during severe or chronic oxidant exposure (27). CAPE incubation significantly restored catalase activity in this study.…”
Section: Discussionmentioning
confidence: 99%